Incidence and influencing factors of kinesiophobia in patients with chronic heart failure: a scoping review - Xiang, Qin; Xiong, Xiao-Yun; Zhang, Mei-Jun; Liu, Si; Chen, Hua; Liu, Meng-Die; Wang, Ying; Yang, Ying (Frontiers in Psychology, 2024)
Kinesiophobia denotes an excessive and irrational apprehension towards physical activity or exercise among patients, stemming from a perception of susceptibility to painful injury or re-injury. Cardiac rehabilitation stands pivotal in the secondary prevention spectrum for individuals with cardiovascular ailments, with exercise constituting a cornerstone of this regimen. However, the emergence of kinesiophobia poses a formidable challenge, diminishing patient adherence to cardiac rehabilitation protocols, particularly among those grappling with chronic heart failure. To bolster exercise-based rehabilitation initiatives in this cohort, a thorough comprehension of the multifaceted factors precipitating kinesiophobia is imperative. This review endeavors to delineate prevailing evidence and prevalence concerning kinesiophobia triggers in chronic heart failure patients, while pinpointing research lacunae for future exploration. Employing a scoping review methodology, our investigation culled data from diverse scholarly databases, including Embase, PubMed, Scopus, CINAHL, Web of Science, Medline, Sinomed, CNKI, Wangfan, and VIP, ultimately incorporating 9 pertinent studies. Our findings underscore a notable prevalence of kinesiophobia in chronic heart failure patients, predominantly influenced by socio-demographic, psychological and cognitive, disease and treatment-related, as well as lifestyle and behavioral factors. Armed with these insights, future interventions can be tailored to mitigate kinesiophobia levels, fostering enhanced engagement in exercise-centric cardiac rehabilitation endeavors among patients grappling with chronic heart failure.